SOCIO-PSYCHOLOGICAL FUNCTIONS OF DECISION-MAKING IN OPTIMIZATION OF MANAGERIAL ACTIVITY - Rasulova Nilufar Tulkunovna; Abdurasulov Olimjon Avalboyevich (American Journals Publishing, 2024)
This article analyzes the role of management in the activity of a leader and its social and psychological aspects. In the analysis, along with theoretical data, scientific and practical recommendations for optimizing the leader's activity are given.
Keywords: Management, psychology, management psychology, decision-making process